Adjustment of the area under the concentration curve by terminal rate constant for bioequivalence assessment in a parallel‐group study of lamotrigine. Issue 3 (17th January 2019) - Yang, Jiansong; Ma, Peiming; Bullman, Jonathan; Nicholls, Andrew; Chen, Chao
Abstract : Aim: A new strength of lamotrigine extended‐release formulation unexpectedly failed to show bioequivalence with the existing strengths at the same dose in a parallel‐group study. We report the post‐hoc analyses conducted to identify the cause and propose an approach for future evaluations in similar situations. Methods: A seemingly bimodal distribution of the half‐life among the study participants prompted the use of terminal‐phase‐rate‐constant‐adjusted area under the concentration curve as the endpoint for bioequivalence assessment. Population pharmacokinetic modelling was also performed to assess the bimodal distribution of apparent clearance and the potential treatment effects on bioavailability. Results: The cause for failing to achieve bioequivalence appeared to be a biased representation of a bimodal clearance distribution between the groups. The pharmacokinetic modelling with a mixture routine identified two subpopulations: 88% had a mean clearance of 1.99 l h −1 ; 12% had a mean clearance of 0.64 l h −1 . The low‐clearance population was unequally represented by 13% and 4% of subjects in the reference and test groups, respectively, and treatment appeared to have no significant effect on oral bioavailability. The bioequivalence comparison using the adjusted area concluded with a 90% confidence interval of 0.91–1.06, suggesting that treatment had no significant effect on bioavailability and the formulations would meet regulatory criteria for bioequivalence. Conclusions: The adjustment of the area under the concentration curve adjusted by terminal‐phase rate constant should be considered for situational application in bioequivalence assessment when there are multiple clearance subpopulations in a parallel‐group study.